Immediate and Subsequent Effects of Matched and Unmatched Stimuli on Targeted Vocal Stereotypy and Untargeted Motor Stereotypy. (July 2013) - Rapp, John T.; Swanson, Greg; Sheridan, Stephanie M.; Enloe, Kimberly A.; Maltese, Diana; Sennott, Lisa A.; Shrader, Lauren; Carroll, Regina A.; Richling, Sarah M.; Long, Ethan S.; Lanovaz, Marc J.
The authors evaluated the effects of matched and unmatched stimuli on immediate and subsequent engagement in targeted vocal stereotypy (Experiment 1) and untargeted motor stereotypy (Experiment 2). Results of Experiment 1 showed that (a) matched stimulation decreased immediate engagement in vocal stereotypy for 8 of 11 participants and increased subsequent engagement in vocal stereotypy for only 1 of the 8 participants and (b) unmatched stimulation decreased immediate engagement in vocal stereotypy for only 1 of 10 participants and did not increase subsequent engagement in vocal stereotypy for this participant. Results of Experiment 2 showed that for 8 of 14 participants, untargeted stereotypy increased when the matched or unmatched stimulus was present, after it was removed, or both. The authors briefly discuss the potential clinical implications of using matched stimulation to decrease vocal stereotypy and limitations of the findings.